Impact of gender mainstreaming process on the achievement of women empowerment in Malaysia - Ismail, Nur Syakiran Akmal (2013)
Gender Mainstreaming (GM) was introduced in 1995 at the Fourth Women Conference in Beijing, China. The objective of its introduction is to achieve gender equality.Malaysia had agreed to implement GM in its policy cycle process.The GM strategies in Malaysia were only being implemented in 2009; however the practice of GM processes had occurred earlier right after gaining its independence. Detailed GM processes were evident in the Sixth Malaysia Plan in 1991.This paper will discuss the process and impact of GM on the achievement of women empowerment in Malaysia. The results of this paper however, showed that women empowerment in Malaysia have managed to achieve up to access level only.